Waste : one woman's fight against America's dirty secret - Flowers, Catherine Coleman (The New Press, 2020)
"Catherine Flowers grew up in Lowndes County, Alabama, a place that's been called "Bloody Lowndes" because of its violent, racist history. Once the epicenter of the voting rights struggle, today it's Ground Zero for a new movement that is Flowers's life's work. It's a fight to ensure human dignity through a right most Americans take for granted: basic sanitation. Too many people, especially the rural poor, lack an affordable means of disposing cleanly of the waste from their toilets, and, as a consequence, live amid filth. Flowers calls this America's dirty secret. In this powerful book she tells the story of systemic class, racial, and geographic prejudice that foster Third World conditions, not just in Alabama, but across America, in Appalachia, Central California, coastal Florida, Alaska, the urban Midwest, and on Native American reservations in the West. Flowers's book is the inspiring story of the evolution of an activist, from country girl to student civil rights organizer to environmental justice champion at Bryan Stevenson's Equal Justice Initiative. It shows how sanitation is becoming too big a problem to ignore as climate change brings sewage to more backyards, and not only those of poor minorities"--